Exploration of pathogenic bacteria from lettuce (Lactuca sativa) in a Canteen at Universitas Padjadjaran - Chan, Rosamond; Syaputri, Yolani; Syamsuri, Rizky Riscahya Pratama; Rossiana, Nia (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Background: Lettuce (Lactuca sativa) is commonly consumed raw as a salad, making it highly susceptible to contamination by pathogenic bacteria. This study aims to identify the presence of pathogenic bacteria on raw lettuce to offer an alternative method for handling these pathogens and improving public health. Method: In this research, lettuce samples were bacteriologically tested to identify the presence of pathogenic bacteria. Isolation was performed using selective media, Salmonella-Shigella (SS) agar and Eosin Methylene Blue (EMB) agar, to obtain pathogenic bacteria. Identification was conducted through macroscopic and microscopic examinations, as well as biochemical tests, including indole, Methyl Red, Voges-Proskauer, citrate, motility, and catalase tests. Results: The results of the study revealed the presence of four bacterial isolates: SS 1, SS 2, EMB 1, and EMB 2. Based on the study and identification using